Feminism and Stereotypical Modeling in the Tourism Packages of the Calabar Festival - Andrew-Essien, Elizabeth; Andrew-Essien, Esekong (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2021)
The various packages that tourism efforts offer often include gaily-clad women who serve promotional purposes. In the same manner, live performances and parades have in recent times progressed towards the objectification of women as viable sexual objects of tourism. From an ethical perspective, the objectification of women in tourism deserves attention when considered in the light of gender discrimination. This paper examines the 32-day Cross River Christmas Festival to highlight the merits and demerits of the objectification of women as attractive products of entertainment in tourism. Four hundred (400) questionnaires were randomly distributed to a cross-section of respondents within the Calabar environs. Findings show that objectification of womanhood has both advantageous and disadvantageous consequences. In the first instance, it is an accepted vehicle for advertising tourism as it sustains the interest of the public. On the other hand, it constitutes a poor basis to reflect African values and morals. Recommendations include the need to bridge Western tourism ideologies to align with the African values in tourism, while decency is advocated for promoting tourism.